الأمن الاقتصادي في ظل الأزمة السورية - رعد خالد; يوسف جنان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يتناول البحث موضوع الأمن الاقتصادي في ظل الأزمة السورية، والذي يعد موضوعاً شائكاً وبالغ الأهمية لكافة القطاعات الاقتصادية لما أصابها من ضرر وخراب أثّر عليها بشكل مباشر أو غير مباشر، وذلك من خلال رصد تلك القطاعات الاقتصادية كلٍ على حدى، وتحديد أولوياتها حسب حاجة كل قطاع تبعاً لطبيعة ودينامية الظروف المحيطة بها. تتألف الدراسة من مقدمة وإطار منهجي، ومحاور رئيسة، تتناول مفهوم الأمن الاقتصادي، وملامح الاقتصاد السوري ما قبل الأزمة، أولويات الأمن الاقتصادي لكافة القطاعات الاقتصادية بشكل مختصر نسبياً، سيناريوهات ما بعد الأزمة، نتائج ومقترحات، وأخيراً الخاتمة. The research addresses the subject of “economic security in the shadow of the Syrian crisis”-which is considered a very tricky however important for all sectors of the economy, especially after the damage and destruction these sectors suffered, which affected them directly or indirectly- by monitoring these economic sectors individually, and setting priorities of each sector according to the nature and dynamics of the ambient conditions. This study consists of an introduction, methodological framework and main focus-points including the study the concept of economic security, a look back at the pre-crisis Syrian economy, relatively briefly, the Economic security priorities for all economic sectors, Post-crisis scenarios, conclusions and proposals, and finally the conclusion.